PERSEPSI MAHASISWA SENIOR DAN JUNIOR TERHADAP PROFESI AKUNTAN - Lydia Setyawardani (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2009)
The purpose of this research is to observe the perception among senior and junior students about accounting profession and the different perception between senior students and junior students regarding accounting profession at regular program in STIESIA Surabaya. This research shows that at regular program, the perception of senior students towards accountant as a profession is lower than junior students. Although the differences are not significant; the research shows that the more senior students get the accounting education, the more they do not like accounting and do not want to have a career as an accountant. It might because the students still do not understand the role the accounting profession play in the environment and accounting profession is not an interesting and doesn’t give them with big salary. But the uniqueness of this research is, the senior students still do not understand that a professional accountant will not work by him or herself. They will always work as team work, and always need the partners or assistants.